A cross-sectional study of COVID-19 testing and disclosure hesitancy: The role of responsibility attribution in South Korea - Minjung Lee (PLoS ONE, 2025)
Efficient and effective public health surveillance during epidemics relies heavily on active and voluntary public participation, including timely COVID-19 testing and disclosure of results to contacts. This study aimed to investigate predictors of COVID-19 testing and disclosure hesitancy, with a focus on the role of responsibility attribution during the early stages of the Omicron epidemic in South Korea. A cross-sectional survey was conducted with 1,000 participants between February 25 and March 2, 2022. Chi-square tests and multivariable logistic regression models were used for analysis. Findings showed that 41.5% of participants expressed hesitancy toward COVID-19 testing, and 59.4% expressed hesitancy toward disclosing test results to contacts. Greater attribution of responsibility to individuals was significantly associated with increased hesitancy toward testing (OR = 0.75, 95% CI = 0.63–0.90, p < 0.001) and disclosure (OR = 0.67, 95% CI = 0.56–0.80, p < 0.001). Conversely, testing acceptance was positively associated with trust in the government (OR = 1.29, 95% CI = 1.07–1.55, p = 0.01), social support (OR = 2.18, 95% CI = 1.73–2.73, p < 0.001), and full vaccination status (OR = 1.98, 95% CI = 1.11–3.50, p = 0.02). Disclosure acceptance was similarly associated with trust in the government (OR = 1.26, 95% CI = 1.05–1.51, p = 0.01) and social support (OR = 2.23, 95% CI = 1.77–2.81, p < 0.001). These results underscore the central role of responsibility attribution in shaping public participation in surveillance efforts. Mitigating excessive individual attribution and fostering a balanced perspective that integrates both personal and contextual factors may enhance public engagement. While attribution remains a key psychological predictor, building trust in government and strengthening social support systems also emerge as important strategies for promoting active and voluntary participation in public health surveillance.